2013
DOI: 10.1007/s13753-013-0010-1
|View full text |Cite
|
Sign up to set email alerts
|

Disaster preparedness: Looking through the lens of hospitals in Japan

Abstract: Critical facilities, such as hospitals, play a crucial role in the socioeconomic and psychological recovery of the population after a disaster. Hospitals are considered important due to their roles in saving lives in the affected population and must be able to withstand hazards and remain functioning during and after a disaster. This article assesses earthquake preparedness of hospitals in eight Japanese cities using a questionnaire survey. The questionnaire consists of six parameters and 21 indicators from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
80
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 9 publications
0
80
0
1
Order By: Relevance
“…Also, approximately all hospitals had notable stores of amenities and facilities such as tents, water reservoirs, folding beds, generators, etc. (14). In the study of Salari et al, Shiraz hospitals had good emergency response plans in terms of admissions, training and maintenance, but were in a moderate level in terms of safety, communications, and transportation, and evacuation conditions (21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, approximately all hospitals had notable stores of amenities and facilities such as tents, water reservoirs, folding beds, generators, etc. (14). In the study of Salari et al, Shiraz hospitals had good emergency response plans in terms of admissions, training and maintenance, but were in a moderate level in terms of safety, communications, and transportation, and evacuation conditions (21).…”
Section: Discussionmentioning
confidence: 99%
“…Results of the Japanese study also indicated that while 80% of studied hospitals had special spaces available for evacuating patients during emergencies, the rest of these hospitals (20%) did not have such spaces, so they were not able to accommodate large numbers of evacuees during emergencies. (14). Hospitals in our study were ranked as weak preparedness hospitals for managing emergency and disaster in domains of procedures, guidelines, plans, human resources, monitoring and evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From these studies, four research studies proposed a model, framework or tool which developed the process of assessing HDR. These model, tools, and framework were as follows: Hospital Safety Index (HSI)(27), Dynamic approach to the seismic resilience of hospitals (45), Measuring framework of the hospital resilience (33), and The indicators for assessing hospital disaster preparedness in Japan (25). Some of the articles did notpresent any tool or model for assessing HDR; however,they consisted relevant indicators or variables to HDR.…”
Section: Thematic Analysismentioning
confidence: 99%
“…There are significant amount of research conducted to understand hospitals response to hazards and some studies containing a tool or instrument like Hospital Safety Index (HSI) as a rapid, reliable, and cost-effective diagnostic tool for assessing the safety of hospital buildings, critical systems and equipment, the availability of supplies, and the emergency and disaster management capacities of the hospital. This tool not only helps to assess safety status, but also helps to evaluate the response capacity of the hospitals (22)(23)(24)(25)(26)(27).Moreover, there are some studies that mentioned instruments for assessing Hospital Disaster Resilience (HDR). In some of them the authors focused on operational characteristics of hospitals; however, the structural and non-structural aspects of hospital resilience were not mentioned in details (28)(29)(30)(31)(32)(33).For instance, Zhong proposed multiple concepts for assessing hospitals resilience in response to disasters in China.…”
mentioning
confidence: 99%